Operational Audit of the Company's Sales Function E-Commerce Diabeaproject - Mulyana Machmud; S. Syamsuddin; Nur Lazimatul Hilma Sholehah; Parmin Ishak (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2021)
The purpose of this study was to determine whether the operational activities implemented by the sales function at the Makassar Diabeaproject company were running effectively. This type of research is a case study—data obtained by conducting documentation and interviews. The data analysis technique was using descriptive analysis based on the audit findings. This study indicates that the sales function's implementation has run quite effectively because it carries out almost all sales function activities. However, there are still some weaknesses that the company has. defects in the form of the absence of criteria guidelines for giving promos or discounts to buyers and no proof of transactions for payments via bank transfer.